PEMBENTUKAN KARAKTER SISWA MELALUI INTERNALISASI NILAI-NILAI ANTI KORUPSI - Achmad Anwar Abidin (Institut Keislaman Abdullah Faqih (INKAFA) Gresik, 2017)
These article discuses about the forming of student’s characters through the internalization of anti-corruption values. In which the form of internalization of the value can be realized with anti-corruption education for children, especially children of elementary school, where they have an important role in the forming and realization of the nation’s future. From this case, it can be seen that corruption prevention efforts might be done in two steps, namely repressive and preventive measures. Repressive measures are carried out by enforcing strict law enforcement by law enforcement officers, and preventive measures are carried out through education. The important values which can be realized in the anti-corruption education process are; responsibility, discipline, honesty, simple life-giving, hard work, self-reliance, fairness and caring. By investing the value through Islamic learning anti-corruption education can be performed to put forward and become one of the main reference curriculum educations in Indonesia.Keywords: Internalization, value, and anti-corruption.